A new species of Paracaprella Mayer, 1890 (Amphipoda: Caprellida: Caprellidae) from southern Brazil - Lacerda, Mariana B.; Masunari, Setuko (Zootaxa, 2014)
A new species of the genus Paracaprella is described based on the specimens associated with the algae Sargassum cymosum and Laurencia obtusa that were collected from infralittoral depths (0.5 to 3.0 m) at Sepultura Beach, Bombinhas and Paciência Beach, Penha, Santa Catarina State, Brazil. This new species differs from the others of the genus by the unique morphology of the males’ gnathopod 2: its propodus has a grasping margin provided with a deep groove. An identification key for Paracaprella species is also presented.